The Impact of Hate Speech on The Halilintar Family's Self-Concept on Instagram Comment Section - Fifi Susanti Wibowo; Rahayu Pujiastuti (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
Hate speech is commonly found in social media comment sections. For recipients of hate speech, it has an impact in the form of a response known as self-concept. The aim of this study is to describe (1) the form of hate speech and (2) the self-concept of the Halilintar family after receiving hate speech in the instagram comment section. This research approach is descriptive qualitative. The data source of this research is the Halilintar family's instagram comment column. The data are in the form of words, phrases, clauses, and sentences in the Halilintar family's instagram comment section that contain hate speech and self-concept. Data collection uses documentation, download, and observation techniques. Data analysis uses descriptive techniques. The data analysis procedure consists of data reduction, data presentation, interpretation, and conclusions. Data validity uses triangulation of theory and method. The results of this study include (1) forms of hate speech in the comment section of the Halilintar family's Instagram, in the form of false or fake news (hoaxes), incitement, threats, defamation, slander, and insults; (2) self-concept in the form of positive self-concept and negative self-concept.